THE CONCEPT OF PLURALISM IN ISLAMIC EDUCATION - Adam, Anas M. (Ar Raniry : International Journal of Islamic Studies, 2017)
Religious pluralisme is a term used to refer to positive attitudes toward world religions (e.g., Islam, Christianity, Hinduism, Budhism, Catholic, etc) with the aim of creating a harmonious, peaceful, and prosperous life within a pluralist society by upholding people's equal rights to live peacefully in this world. The aim of this article is to elaborate on the concept of religious pluralism and its relation to Islamic education. There have been a controversy caused by the differing definitions of religious pluralism, which has led to certain misconceptions and hence its alienation from Islamic education in general. In the face of such challenges, efforts must continually be made to foster mutual understanding and respect between people of different religions in order to avoid potential conflicts, either between people embracing different religions or people within the same religion. It is this positive awareness which religious pluralism seeks to foster. Thus, incorporating the concept of pluralism into Islamic education is a must, especially by making change to the system of Islamic education which for a long time has focused only on building individual or communal piety. The new priority should be given to the creation of social sensitivity toward pluralism, either through cultural, language, or religious interventions. This all aims at reinforcing the notion of Islam as Rahmatallil’alamin.